Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Li, Shuang-Qing; Xiao, Yan; Huang, Hai-Long; Luo, Zhen; Sun, Tao-Ran; Gao, Hua-Yang; Wang, Xin-Wei; Jiang, Hai-Bo (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a "new" source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut-ureA) that cannot use urea. However, the growth rate of Mut-ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium-derived nitrogen was not available to Mut-ureA. Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a "new" nitrogen source, benefiting in particular populations of surrounding phytoplankton species.